Bilateral orbital cellulitis due to Neisseria gonorrhoeae and Staphylococcus aureus: a previously unreported case - Raja, N.S.; Singh, N.N. (Microbiology Society, 2005)
Cellulitis of the orbit is a common cause of proptosis in children, and also frequently arises in the elderly and the immunocompromised. The condition is characterized by infection and swelling of the soft tissues lining the eye socket, pushing the eye ball outwards and causing severe pain, redness, discharge of pus and some degree of blurred vision. There is a small risk of infection spreading to the meninges of the brain and causing meningitis. This paper reports the case of an adult in whom polymicrobial bilateral orbital cellulitis had developed due to Staphylococcus aureus and Neisseria gonorrhoeae infection. N. gonorrhoeae infections are acquired by sexual contact. Although the infection may disseminate to a variety of tissues, it usually affects the mucous membranes of the urethra in males and the endocervix and urethra in females. To the authors' knowledge this is the first report of polymicrobial bilateral orbital cellulitis due to S. aureus and N. gonorrhoeae in medical literature.